2013
DOI: 10.1002/ece3.763
|View full text |Cite
|
Sign up to set email alerts
|

Functional similarity and molecular divergence of a novel reproductive transcriptome in two male‐pregnant Syngnathus pipefish species

Abstract: Evolutionary studies have revealed that reproductive proteins in animals and plants often evolve more rapidly than the genome-wide average. The causes of this pattern, which may include relaxed purifying selection, sexual selection, sexual conflict, pathogen resistance, reinforcement, or gene duplication, remain elusive. Investigative expansions to additional taxa and reproductive tissues have the potential to shed new light on this unresolved problem. Here, we embark on such an expansion, in a comparison of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 85 publications
(164 reference statements)
3
17
0
Order By: Relevance
“…As documented previously in S. scovelli and S. floridae [52], two similar astacin-like metalloproteases demonstrated strikingly opposite patterns of gene expression: one markedly pregnancy-enriched and the other highly pregnancy-depressed (Table 2, Table 3, Fig. 7b, c).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…As documented previously in S. scovelli and S. floridae [52], two similar astacin-like metalloproteases demonstrated strikingly opposite patterns of gene expression: one markedly pregnancy-enriched and the other highly pregnancy-depressed (Table 2, Table 3, Fig. 7b, c).…”
Section: Resultssupporting
confidence: 75%
“…Previous work identified members of the astacin-like metalloprotease gene family as candidates for playing a functional role in male pregnancy [18, 52]. We confirmed extreme transcriptional differences for two of these patristacins between brood pouch tissue of pregnant and non-pregnant males (see “Differential expression analysis” section) and set out to characterize the distribution of this gene family in the Gulf pipefish and other teleost genomes.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…Molecular tools, as well as enabling phylogenetic and conservation genetic studies of syngnathids, offer an unprecedented opportunity to resolve the genetic basis of male pregnancy (Mobley, Small & Jones, ). For example, transcriptomic and other gene‐expression studies of the brood pouch during pregnancy have identified genes putatively involved in a variety of pouch functions (Melamed et al ., ; Harlin‐Cognato et al ., ; Small et al ., ). Given that the physiology of the pouch in some species appears to vary throughout pregnancy, an approach which has proved particularly powerful is to use RNA sequencing (RNA‐seq) at a number of reproductive stages to compare gene expression at a fine scale as embryos develop (Whittington et al ., ).…”
Section: Where To Next For Syngnathid Reproduction Research?mentioning
confidence: 97%